Sinergi Generasi Muda dan UMKM dalam Memperkuat Pertahanan Keamanan Digital Desa Lubuk Banjar - Nurfadila, Nova; Nugraha, M. Auriel; Mardalena, Ervin; Akbar, Ali; Dewi, Rosmala; Priharti, RR. Dimas Veronica (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Digital transformation has influenced educational activities and Micro, Small and Medium Enterprises (MSMEs) in rural areas, including in Lubuk Banjar Village. The use of digital technology by educators and MSME actors facilitates learning and business management, but also increases the risk of digital security threats such as account hacking, online fraud and data misuse. This community service activity aims to improve digital literacy and awareness among educators and MSME actors as part of efforts to strengthen village defence and security. The method of implementation was through socialisation and interactive training activities involving the village's younger generation as facilitators and mentors, with material covering secure password management, digital fraud prevention, and digital asset protection. The activities were carried out through material presentations, discussions, case simulations, and hands-on practice. The results of the activities showed an increase in participants' understanding of the importance of maintaining digital account security, the ability to recognise various forms of online fraud, and awareness of the need to implement basic cybersecurity measures in educational and business activities. The synergy between the younger generation, educators, and MSME actors plays a strategic role in strengthening the digital resilience and security of Lubuk Banjar Village in a sustainable manner.